1973
DOI: 10.1002/1097-4679(197301)29:1<78::aid-jclp2270290128>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Personality characteristic differences between alcoholics who leave treatment against medical advice and those who don't

Abstract: JACK SIDMAN AND RUDOLF MOOSrived from frequency ratings of 70 items of staff t o patient helping and 70 items of patient to patient helping made by patients from 9 different wards. A number of significant relationships were found, and some of the results were discussed in terms of their implications for possibly obtaining more effective treatment outcome by changing social psychological atmosphere through the mediating variables of patient and staff helping behaviors. 8. Moos, R. H. and SCHWARTZ, J. Treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1975
1975
2000
2000

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Two studies found that patients who left early were more defensive and more apt to deny their discomfiture (Mozdzierz, Macchitelli, Conway, & Krauss, 1973;Nelson & Hoffmann, 1972). The alcoholic inpatient's cognitive style is also involved in whether he stays in the hospital.…”
Section: Alcoholismmentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies found that patients who left early were more defensive and more apt to deny their discomfiture (Mozdzierz, Macchitelli, Conway, & Krauss, 1973;Nelson & Hoffmann, 1972). The alcoholic inpatient's cognitive style is also involved in whether he stays in the hospital.…”
Section: Alcoholismmentioning
confidence: 99%
“…It turned out to be important in 24 out of 26 studies (92.3%) that considered it (Blenkner, 1954;Brown & Kosterlitz, 1964;Chappel et al, 1973;Errera et al, 1967;Freedman, et al, 1958;Garfield et al, 1963;Gibby et al, 1954;Heilbrun, 1962;Heine & Trosman, 1960;Hewitt, 1969;Hiler, 1959;Katz & Solomon, 1958;Kissin et al, 1973;Lake & Levinger, 1960;E. Meyer et al, 1967;Miller et al, 1968;Mozdzierz et al, 1973;Nelson & Hoffman, 1972;Pittel et al, 1972;Rickels, 1968;Robson et al, 1965;Taulbee, 1958;Wittkower & Russell, 1956) and irrelevant in only 2 out of 24 studies (8.3%) (Affleck & Garfield, 1961;Lorr et al, 1958).…”
Section: Psychological Mindednessmentioning
confidence: 99%
“…A diagnosis of sociopathic personality was linked with discharge against medical advice by Greenwald & Bartemeier (1963) while Altman et al (1972ft) linked discharge against advice with 'impulsivity' and a disregard for rules and regulations, a conclusion which seems somewhat circular. When more specific psychological characteristics have been studied, denial of illness 787 (Mozdzierz et al 1973) and lack of insight in psychosis (Nelson, 1975;Lin et al 1979;Marder et al 1983; Bartko et al 1988) have been linked to poor compliance. More detailed studies of patient attitudes to illness and treatment have been conducted by Soskis & Bowers (1969) and McGlashan & Carpenter (1981).…”
Section: Introductionmentioning
confidence: 99%
“…Huber and Danahy (1975) found that only the Psychopathic Deviate (Pd) scale significantly differentiated completers from noncompleters. Mozdzierz, Macchitelli, Conway, and Krauss (1973) found that noncompleters tended to produce more defensive profiles than did completers, whereas Krasnoff…”
mentioning
confidence: 99%